2017
DOI: 10.1002/jcop.21933
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the processes linking public stigma and self‐disclosure among college students with mental illness

Abstract: This study investigated predictors of self‐disclosure among college students with mental illness. Participants were 1,393 current college students with a mental illness at 5 universities. Moderated mediation tests were used to analyze the data. Findings of the analysis reveal that public stigma is associated with mental illness disclosure among college students in part because it is associated with an increased perceived stress burden, particularly among men. Implications for future research and program develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
1
14
0
1
Order By: Relevance
“…eating disorder), and public stigma towards issues perceived as masculine appears to be higher than towards those perceived as feminine [87, 88]. There are also gender differences in perceived stigma, where men may experience elevated stress regarding disclosing mental health issues in comparison to women [89]. Anticipated and perceived stigma are common manifestations of mental health-related stigma, contributing to fear of acknowledging one’s mental health issue and possibly leading to shame and avoidance regarding seeking mental health care [90, 91].…”
Section: Practical Applicationsmentioning
confidence: 99%
“…eating disorder), and public stigma towards issues perceived as masculine appears to be higher than towards those perceived as feminine [87, 88]. There are also gender differences in perceived stigma, where men may experience elevated stress regarding disclosing mental health issues in comparison to women [89]. Anticipated and perceived stigma are common manifestations of mental health-related stigma, contributing to fear of acknowledging one’s mental health issue and possibly leading to shame and avoidance regarding seeking mental health care [90, 91].…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Results of the study revealed that male students with disabilities were more willing to disclose to their professors compared to their female counterparts. As reported earlier, women are more willing to disclose mental illness than men (Brown et al, 2018). These findings are not consistent with past research regarding gender.…”
Section: Discussionmentioning
confidence: 53%
“…Research indicates that compared to men, women are generally more open to reveal their personal issues and are more likely to seek help when faced with stressful life experiences (Turner & Brown, 2010; Wismeijer et al, 2009). Specifically, Brown et al (2018) found that women were more willing to disclose mental illness than men. However, Hartnett and colleagues (2014) found no difference on accommodation requests between male and female participants.…”
Section: Individual Factorsmentioning
confidence: 99%
“…Studi Brown et al (2018) pada 1.393 mahasiswa dengan penyakit mental di Universitas menggunakan tes mediasi yang dimoderasi untuk analisis data. Hasil studi menunjukkan bahwa stigma masyarakat berhubungan dengan self-disclosure mahasiswa yang memiliki penyakit mental, terutama bagi mahasiswa pria.…”
Section: Hasil Dan Diskusiunclassified